Inside the Family Firm - Morten Bennedsen; Kasper Nielsen; Francisco Pérez-González; Daniel Wolfenzon (Copenhagen Business School (CBS), Department of Economics, 2005)
This paper uses a unique dataset from Denmark to investigate (1) the role of family characteristics in corporate decision making, and (2) the consequences of these decisions on firm performance. We focus on the decision to appoint either a family or an external chief executive officer (CEO). We show that a departing CEO's family characteristics have a strong predictive power in explaining CEO succession decisions: family CEOs are more frequently selected the larger the size of the family, the higher the ratio of male children and when the departing CEOs had only had one spouse. We then analyze the impact of family successions on performance. We overcome endogeneity and omitted variables problems of previous papers in the literature by using the gender of a departing CEO's first-born child as an instrumental variable (IV) for family successions. This is a plausible IV as male first-child family firms are more likely to pass on control to a family CEO than female first-child firms, but the gender of the first child is unlikely to affect firms' performance. We find that family successions have a dramatic negative causal impact on firm performance: profitability on assets falls by at least 6 percentage points around CEO transitions. These estimates are significantly larger than those obtained using ordinary least squares. Finally, our findings demonstrate that professional nonfamily CEOs provide extremely valuable services to the organizations they work for.
hdl:10398/7594
Keywords: G32; G34; M13; 330; Family firms; Successions; CEO turnover; governance